An Application of Lean Six Sigma Logistics for an Improvement for Supplies Warehouse in a Body & Paint Repairing Center - Nanthasamreong, Natthapong; Payatham, Pornnapa; Suwandee, Maneerat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2021)
This research aimed to study the working condition and apply the lean six sigma logistics concept in controlling and reducing cost in a supplies warehouse of the body & paint repairing center. The defining and measuring of initial condition result revealed that there were waiting wastes and excessive colors requisition. After analyzing the problems, the root causes of problem were inappropriate warehouse managing and lack of working standards. Therefore, the processes were improved by re-layout of warehouse areas and used the location identification banners as a visual control standard. In addition, the color mixing standard of operation for painting technician was established. The improvement results revealed that supplies requisition time reduced 100.18 seconds (40.32 %) and average total cost of painting colors reduced 5,135.90 Baht per car (22.13 %) or can reduce 1,540,770 Baht per year.